STOCHASTIC ANALYSIS OF OUTAGE PROBABILITY OF THE CASCADED RAYLEIGH-RICIAN FADING CHANNEL USING PADÉ APPROXIMATION METHOD (Nigerian Journal of Technology, 2024)
The dominance of wireless communication (WC) is evident in all areas of life such as Information and Communication Technology (ICT), research, business, academia, etc. However, modelling analysis of WC has been a serious challenge when it involves diversity combining. Previous work has attempted to solve this problem using approximation techniques. These approximation techniques seem to be complex and may be difficult to interpret. The existing practice of using the Probability Density Function (PDF) to analyse multipath fading in a diversity-rich environment is ineffective to handle cascaded fading channels. The current work proposed the Padẻ Approximation (PA) technique to mitigate the problem. The PA was developed from the generated Moment Generating Function (MGF) by truncating the Taylor series to obtain a rational expression. The approximated rational expressions obtained were transformed into PDF, Cumulative Density Function (CDF) and Outage Probability (). The results show that the  reduces as the threshold value increases. The numerical results also shows that the diversity techniques is effective in combating fading because as the number of paths increases, the  reduces. The  reduces by 17.56% at L=4 from 90.83% at L=1 when there is no diversity. PA is a useful approximation to analyse the behavior of cascaded Rayleigh-Rician channel.